A knowledge management approach to citizen relationship management in e-government context - Norshidah, Mohamed; Nor Shahriza, Abdul Karim; Mohamed Razi, Mohamed Jalaldeen (The Social Sciences Reserach Society, 2013)
With globalization, the Internet and increasing demands from citizens,governments around the world are pressured to serve citizens and businesses electronically thus to adopt policies that reduce bureaucracy and be agile to changes in structure. This entails that the electronic government that has been serving as a means for support in the last decade is no longer adequate. Government agencies are expected not to be working in silos. More and more government operations are expected to be networked and interconnected. Increasingly, governments are pressured to have a single view of citizens through Citizen Relationship Management (CzRM). The paper proposes a conceptual framework on CzRM using the knowledge management approach. It builds on prior literature in knowledge management. This constitutes knowledge characteristics, knowledge management strategy, knowledge management processes and knowledge management technological infrastructure in managing citizen relationship. The implications for research and practice are further discussed